Enhanced THz resonance based on the coupling between Fabry–Perot oscillation and dipolar-like resonance in a metamaterial surface cavity. (9th November 2015) - Zhang, Yaxin; Xu, Gaiqi; Qiao, Shen; Zhou, Yucong; Wu, Zhenhua; Yang, Ziqiang
Abstract: We presented an enhanced resonance with ultra-wide band in the terahertz (THz) regime in a THz metamaterial system composed of a pair of circular rings arrays which act as two opposite mirrors. The two opposite mirrors, both of which will induce a dipolar-like resonance under the incident wave, together with the gap between them will constitute a Fabry–Perot cavity which contributes to a Fabry–Perot oscillation in the system. These two kinds of resonant modes, the dipolar-like resonance and Fabry–Perot oscillation, can be coupled with each other in an optimized structure, which leads to an enhanced electromagnetic resonance. From the experimental results, it can be found that such coupling leads to a nearly zero transmission zone with 0.12 THz bandwidth which is much better than individual conventional metamaterial system. This coupling mechanism could provide a new way for the realization of strong resonance, which shows great potential for THz pass-band or stop-band filters, THz resonators, THz absorbers, frequency selective devices and so on.